2017
DOI: 10.3390/molecules22091408
|View full text |Cite
|
Sign up to set email alerts
|

Sigma Receptor (σR) Ligands with Antiproliferative and Anticancer Activity

Abstract: Sigma receptor (σR) ligands have proven to be useful as cancer diagnostics and anticancer therapeutics and their ligands have been developed as molecular probes in oncology. Moreover, various σR ligands generate cancer cell death in vitro and in vivo. These σR ligands have exhibited promising results against numerous human and rodent cancers and are investigated under preclinical and clinical study trials, indicating a new category of drugs in cancer therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 122 publications
(175 reference statements)
0
23
0
Order By: Relevance
“…Interest in SRs has increased substantially over the years, as documented by the high number of research papers and reviews published, patents registered ( Bowen, 2000 ; Bourrie et al, 2004 ; Collina et al, 2013 , 2017a ; Georgiadis et al, 2017 ), as well as by the presence of SR modulators in the pipelines of pharmaceutical industries 1 , 2 , 3 ( Accuronix Therapeutics, 2018 ; Anavex Pipeline, 2018 ; Context Therapeutics, 2018 ).…”
Section: Er Stress and Srsmentioning
confidence: 99%
“…Interest in SRs has increased substantially over the years, as documented by the high number of research papers and reviews published, patents registered ( Bowen, 2000 ; Bourrie et al, 2004 ; Collina et al, 2013 , 2017a ; Georgiadis et al, 2017 ), as well as by the presence of SR modulators in the pipelines of pharmaceutical industries 1 , 2 , 3 ( Accuronix Therapeutics, 2018 ; Anavex Pipeline, 2018 ; Context Therapeutics, 2018 ).…”
Section: Er Stress and Srsmentioning
confidence: 99%
“…The overexpression of the sigma-2 receptor in various types of cancers, including breast carcinoma, melanoma, prostate cancer, pancreatic tumors, and brain tumors [14, 27], has caused sigma-2 receptor ligands to be potential drugs for monitoring and treating cancer [18, 28]. Previous studies have shown that several derivatives of the high affinity sigma-2 receptor agonist PB28 (1-cyclohexyl-4-[3-(5-methoxy-1,2,3,4-tetrahydronaphthalen-1-yl)propyl]piperazine), have the ability to inhibit the growth of pancreatic cancer [20, 25] and the neuroblastoma SK-N-SH cell line [19].…”
Section: Resultsmentioning
confidence: 99%
“…The overexpression of the sigma-2 receptor by cancer cells has been reported in several types of tumors, including breast, pancreatic, and brain tumors [14, 18]. This has led to the discovery of sigma-2 receptor ligands as potential compounds in cancer diagnosis and therapy [28]. Among the many sigma-2 receptor ligands, serial analogues of PB28 have been developed and their potential for cancer imaging and therapy, addressed [15, 16, 1820, 24, 25, 30].…”
Section: Discussionmentioning
confidence: 99%
“…Although clinical trials failed to show satisfactory efficacy in the treatment of psychiatric disorders, the drug was well-tolerated and non-toxic in humans. The lack of side-effects; the strong and immediate effects of siramesine on lysosome acidification, trafficking, and autophagy activation; and its predicted capacity to target the nsp16/nsp10 interface might open new avenues for the therapeutic consideration of this lysosomotropic agent and/or closely related sigma-2-receptor-targeting drugs [66,[90][91][92].…”
Section: Siramesinementioning
confidence: 99%